FEED INTAKE AND GROWTH OF VANNAMEI SHRIMP (Litopenaeus vannamei) WITH THE ADDITION OF DIFFERENT ATTRACTANT SOURCES IN SELF-PREPARED FISH FEED - Saridu, Siti Aisyah; Budiyati, Budiyati; Leilani, Ani; Alauddin, Muhammad Hery Riyadi; Rasnijal, Muhammad; Wahid, Eriyanti; Supryady, Supryady; Regan, Yip (Universitas Mataram, 2025)
One of the issues in aquaculture activities is the high cost of commercial feed, and self-prepared feed can be one of the solutions. Efforts to improve feed utilization in cultured organisms include the use of stimulants known as attractants. The objective of this study is to observe the use of different attractant sources in self-prepared feed for whiteleg shrimp (Litopenaeus vannamei) by examining feed consumption, feed conversion ratio (FCR), and the growth of the shrimp. The treatments in this study consisted of feed without the addition of attractants (A), feed with the addition of squid meal attractant (B), shrimp head meal (C), and rebon (small shrimp) meal (D). Whiteleg shrimp (DOC 30) with an average weight of 2.96±0.21 g were reared in aquariums, with each treatment consisting of four replicates. After the rearing period, the feed intake for treatments A, B, C, and D was 0.156 g/shrimp, 0.184 g/shrimp, 0.181 g/shrimp, and 0.167 g/shrimp, respectively. The feed conversion ratio (FCR) obtained was 1.8, 1.4, 1.2, and 1.3, respectively. The absolute growth for the four treatments was 1.092 g/shrimp, 1.632 g/shrimp, 1.779 g/shrimp, and 1.506 g/shrimp, respectively. Statistical analysis showed no significant differences among the four treatments (P>0.05) in terms of feed consumption, FCR, and growth. The results of this study highlight the potential use of shrimp head meal, which is a waste product, as an attractant and a protein source.